Surgical rehabilitation of swallowing with polydimethylsiloxane injections after open partial horizontal laryngectomy: Long‐term functional results and quality of life. Issue 4 (23rd December 2020) - Mattioli, Francesco; Fernandez, Ignacio Javier; Bassano, Edoardo; Luppi, Maria Pia; Bonali, Marco; Ghidini, Angelo; Trebbi, Marco; Bergamini, Giuseppe; Presutti, Livio; Botti, Cecilia
Abstract: Background: Swallowing disorders are common problems after partial laryngectomy. The aim of this study is to illustrate the long‐term functional results of rehabilitation of swallowing by polydimethylsiloxane (PDMS) injection. Methods: Twenty‐eight patients with dysphagia after partial laryngectomy who underwent injection of PDMS for rehabilitation of swallowing were included in the study. Impairment of swallowing and quality of life (QoL) were investigated with questionnaires: M. D. Anderson Dysphagia Inventory (MDADI) and Performance Status Scale for Head and Neck Cancer (PSS‐HNC). Functional results at fiberoptic endoscopic evaluation of swallowing (FEES) were analyzed using a modified penetration‐aspiration scale. Results: Mean follow‐up was 8.5 years. Twenty‐six patients showed an improvement at questionnaires ( p < 0.001). Median improvement was 6 ( p < 0.001) in the modified penetration‐aspiration scale. Total laryngectomy was required in one patient. Conclusions: PDMS injection is a good option for rehabilitation of swallowing in case of dysphagia after partial laryngectomy. It improves QoL and the results persist after a long follow‐up period.